Nickel foam and stainless steel mesh as electrocatalysts for hydrogen evolution reaction, oxygen evolution reaction and overall water splitting in alkaline media - Hu, Xiaoyan; Tian, Xuemei; Lin, Ying-Wu; Wang, Zhonghua (RSC advances, 2019)
In this work, several commonly used conductive substrates as electrocatalysts for hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) under alkaline conditions were studied, including nickel foam (Ni foam), copper foam (Cu foam), nickel mesh (Ni mesh) and stainless steel mesh (SS mesh). Ni foam and SS mesh are demonstrated as high-performance and stable electrocatalysts for HER and OER, respectively. For HER, Ni foam exhibited an overpotential of 0.217 V at a current density of 10 mA cm −2 with a Tafel slope of 130 mV dec −1 , which were larger than that of the commercial Pt/C catalyst, but smaller than that of the other conductive substrates. Meanwhile, the SS mesh showed the best electrocatalytic performance for OER with an overpotential of 0.277 V at a current density of 10 mA cm −2 and a Tafel slope of 51 mV dec −1 . Its electrocatalytic performance not only exceeded those of the other conductive substrates but also the commercial RuO 2 catalyst. Moreover, both Ni foam and SS mesh exhibited high stability during HER and OER, respectively. Furthermore, in the two-electrode system with Ni foam used as the cathode and SS mesh used as the anode, they enable a current density of 10 mA cm −2 at a small cell voltage of 1.74 V. This value is comparable to or exceeding the values of previously reported electrocatalysts for overall water splitting. In addition, NiO on the surface of Ni foam may be the real active species for HER, NiO and FeO x on the surface of SS mesh may be the active species for OER. The abundant and commercial availability, long-term stability and low-cost property of nickel foam and stainless steel mesh enable their large-scale practical application in water splitting. Efficient electrocatalytic overall water splitting is achieved with commercially-available and low-cost nickel foam and stainless steel mesh as cathode and anode electrodes.